Jewish and Israeli law an introduction - Shetreet, Shimon 1946-; Homolka, Walter 1964- (De Gruyter, 2017)
This book provides a concise introduction to the basics of Jewish law. It gives a detailed analysis of contemporary public and private law in the State of Israel, as well as Israel’s legal culture, its system of government, and the roles of its democratic institutions: the executive, parliament, and judiciary. The book examines issues of Holocaust, law and religion, constitutionalization, and equality. It is the ultimate book for anyone interested in Israeli Law and its politics